MODEL PENGORGANISASIAN PROSES PENDIDIKAN ANAK USIA DINI (PAUD) PADA RAUDHATUL ATHFAL 3 PALEMBANG - Leny Marlina (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
Organizing is a process of determining and dividing work carried out by several people involved in an organization or institution. Raudhatul Athfal Perwanida 3 Palembang is an institution that aims to develop various potentials of children from an early age and already has a number of achievements, but when compared to the age of its establishment and operation, it looks not optimal, especially considering Raudhatul Athfal Perwanida 3 Palembang is in the middle of the city and in the UIN Raden Fatah environment. Palembang. This lack of maximum achievement is partly influenced by the organization of the educational process. This type of research is a qualitative intrinsic case study with inductive thinking logic. The techniques for determining the source of the data were purposive sampling and snowball sampling. Data collection techniques use observation, interviews, documentation, and triangulation both data sources and data collection techniques. For data analysis techniques through data reduction (data reduction), data display (data display), and data verification. The level of accuracy and credibility of the findings is carried out through several strategies, namely: member checking, triangulation, and auditing. The results of the research show that most of the organization of the Early Childhood Education (PAUD) process at Raudhatul Athfal Perwanida 3 Palembang has been carried out even though there are still obstacles that sometimes unexpectedly hinder or disrupt activities in various activities or programs that have been arranged by the school. This institution also has character with its religious content.. This is influenced by several factors, namely the frequent change of foundation managers (Dharma Wanita) in accordance with the leadership of UIN Raden Fatah Palembang, an unclear management system, not yet developed a common vision for all members involved, and a conducive environment for students (children). ) and educators (teachers) in carrying out the educational process.